A comprehensive view of competitive diving - Billingsley, H. (Hobie's Diving Academy, 2006)
This book of nearly 300 pages and 14 chapters was forty years in the making and was written with the purpose of offering a source of information concerning all of the phases found in competitive diving from which coaches and divers can form a solid base to obtain a higher level of performance.